Respuesta :
Combining the fractions gives
[tex]\dfrac{a^2}{bc}+\dfrac{b^2}{ac}+\dfrac{c^2}{ab}=\dfrac{a^3+b^3+c^3}{abc}[/tex]
Since [tex]a+b+c=0[/tex], we also have
[tex](a+b+c)^3=0[/tex]
[tex]a^3+b^3+c^3+3a^2b+3a^2c+3ab^2+3b^2c+3ac^2+3bc^2+6abc=0[/tex]
If we add and subtract the last 7 terms of the left hand side to/from the numerator, we get
[tex]\dfrac{(a+b+c)^3-(3a^2b+3a^2c+3ab^2+3b^2c+3ac^2+3bc^2+6abc)}{abc}[/tex]
[tex]=-3\dfrac{a^2b+a^2c+ab^2+b^2c+ac^2+bc^2+2abc}{abc}[/tex]
[tex]=-3\dfrac{(a+b)(a+c)(b+c)}{abc}[/tex]
Also because [tex]a+b+c=0[/tex], we have
[tex]\begin{cases}a=-(b+c)\\b=-(a+c)\\c=-(a+b)\end{cases}[/tex]
so we find that
[tex]-3\dfrac{(a+b)(a+c)(b+c)}{abc}=-3\dfrac{(-c)(-b)(-a)}{abc}=3\dfrac{abc}{abc}=3[/tex]